2019
DOI: 10.1039/c9sc00155g
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of functionalized nitrogen-containing polycyclic aromatic hydrocarbons and other prebiotic compounds in impacting glycine solutions

Abstract: Impacting glycine mixtures could have resulted in the shock synthesis of NPAHs and other prebiotic compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 89 publications
(112 reference statements)
0
33
0
Order By: Relevance
“…In the case of V-RDAC simulations, one route to develop DFTB parameter sets tuned for shearing conditions would be to force-match the DFTB repulsive potential in eqn (1) to forces from a V-RDAC simulation performed at a DFT level of theory. 23,24,75 Iterative renement schemes that use DFTB-based QMD as a driver to sample new congurations for which one obtains forces from DFT-level single-point calculations is another promising path towards a semi-automated DFTB model development cycle.…”
Section: General Simulation Detailsmentioning
confidence: 99%
See 3 more Smart Citations
“…In the case of V-RDAC simulations, one route to develop DFTB parameter sets tuned for shearing conditions would be to force-match the DFTB repulsive potential in eqn (1) to forces from a V-RDAC simulation performed at a DFT level of theory. 23,24,75 Iterative renement schemes that use DFTB-based QMD as a driver to sample new congurations for which one obtains forces from DFT-level single-point calculations is another promising path towards a semi-automated DFTB model development cycle.…”
Section: General Simulation Detailsmentioning
confidence: 99%
“…37 Simulations modeling impacting glycine-water mixtures have shown that even higher pressures and temperatures (48 GPa, 3000 K) can drive the formation larger oligomeric structures that spontaneously rearrange into polyaromatic molecules upon adiabatic expansion. 24 Polymerization of dry glycine to form dimers up to 10-mers have also been observed under more modest static pressures ranging from 5-100 MPa at elevated temperatures (423 K) over time frames of 1-32 days. 17 Elevated temperatures appear necessary to drive oligomerization in pure glycine under hydrostatic conditions as Hinton et al showed that crystalline a-glycine is largely unreactive at room temperature when compressed up to 50 GPa based on Raman spectroscopy and Xray diffraction measurements.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…For example, once created, the protein forming amino acid glycine has to do something more to form life. It has been pointed out that, if glycine formed on a comet and was delivered to Earth via an impact event, then the energy delivered in that impact may drive further reactions [17]. Therefore, you start with one piece of knowledge, then have to add another, and another, following a path, which may or may not be the right one in terms of the origin of life.…”
Section: Introductionmentioning
confidence: 99%